Bogoslovs'ki rozdymi: schidnojevropejs'kyj žurnal teologiï = Theological reflections : Eastern-European journal of theology (Eastern European Institute of Theology, 2020)
"Theological Reflections: Eastern European Journal of Theology is a peer-reviewed, open-access scholarly journal that aims to establish itself as an open platform for discussing diverse theological issues, primarily in the context of the Evangelical-Protestant tradition. The journal publishes original articles in biblical studies, systematic, historical, and practical theology, and related areas of study"